Assessment of aortic annulus dimensions for transcatheter aortic valve replacement (TAVR) with high-pitch dual-source CT: Comparison of systolic high-pitch vs. multiphasic data acquisition. Issue 133 (December 2020) - Capilli, Fabio; Benndorf, Matthias; Soschynski, Martin; Hagar, Muhammad Taha; Kharabish, Ahmed; Neumann, Franz-Josef; Pache, Gregor; Schlett, Christopher L.; Bamberg, Fabian; Krauss, Tobias
Highlights: For a precise pre-interventional TAVI planning, the use of multi-detector computed-tomography (MDCT) is recommended. A high-pitch CTA protocol delivers an adequate prosthesis size selection for TAVI procedure compared to a multiphase CTA. In selected patients with sinus rhythm the multiphase CTA of the aortic annulus is not absolutely necessary and therefore the radiation dose can be reduced significantly. Abstract: Objectives: To evaluate a systolic ECG-gated high-pitch aortoiliac computed tomography (CT) angiography for planning transcatheter aortic valve implantation (TAVI). Methods: Patients referred for TAVI underwent a combined CT imaging with retrospective, multiphasic ECG-gating of the heart and systolic ECG-gated high-pitch aortoiliac CT angiography. Consecutive patients were retrospectively included in this study group. Heart rate (HR) and heart rate variability (HRV) were assessed during the high-pitch ECG prediction phase. Aortic annulus area (AAA) was planimetrically quantified on both datasets. While only one moment of cardiac cycle was available for measurements in the high-pitch CT, the point of time in the multiphasic CT was chosen, where AAA yielded maximum size. Hypothetical prosthesis sizing was compared between multiphasic vs. high-pitch CT. Results: Among 61 patients (44.2 % men, mean age: 83.3 ± 5.5 years) average heart rate and HRV were 71.0 ± 13.4 bpm and 7.3 ± 8.5 bpm. 20 patients (32.7 %) had atrial fibrillation at the time of image acquisition. There was a strong correlation of AAA as derived from multiphasic vs. the high-pitch CT (r = 0.98). The difference in AAA was 10.5 ± 17.1mm 2 (455.1 ± 83.0 mm 2 for multiphasic vs. 444.5 ± 87.2 mm 2 for high-pitch CT) and did not reach statistical significance (p = 0.08). Hypothetical prosthesis sizing showed an agreement in 55 of 61 patients (90.2 %). A sizing based on the high-pitch CT resulted in smaller prosthesis choice in 6 patients, all of them suffering from atrial fibrillation. Mean effective radiation dose was 10.9 ± 6.1 mSv for cardiac CTA and 4.1 ± 1.0 mSv for high-pitch CTA. Conclusion: For patients with sinus rhythm, systolic high-pitch aortoiliac CTA provides adequate prosthesis size selection as compared with multiphasic ECG-gated cardiac CTA and may result in significantly reduced radiation exposition.